Ответы 1

  • 5/6 * (1/5n + 6) - 2/3 * (9 - 1/2n) + 5/8 * (4/5n - 8) = 5/6 * 1/5n + 5/6 * 6 - 2/3 * 9 - 2/3 * (-1/2n) + 5/8 * 4/5n + 5/8 * (-8) = 1/6n + 5 - 6 + 1/3n + 1/2n - 5 = 1/6n + 5 - 6 + 2/6n + 3/6n - 5;1/6n + 5 - 6 + 2/6n + 3/6n - 5;1/6n + 2/6n + 3/6n = -5 + 6 + 5;1n = 6;n = 6 / 1;n = 6.
    • Автор:

      alex76
    • 3 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years